Electrical Properties of Chemically Synthesized Polypyrrole Pellets and Gamma-Ray Induced Polypyrrole Composite Films - Harun, Mohd Hamzah (2007)

(untitled)
The polypyrrole, PPy conducting polymer pellets and PVA-PPy-FeCl3 composite polymer films have been prepared by using pyrrole, Py monomer, polyvinyl alcohol as polymer binder for polypyrrole composite, and iron (III) chloride, FeCl3 as oxidizing and doping agent by conventional technique; chemical polymerization method. Further, PVA-PPy-CH and PVA-PPy-TCA composite films have been prepared by utilizing Py monomer and doping agents of chloral hydrate, CH and trichloroacetic acid, TCA respectively via gamma irradiation technique. The influence of composition of doping agent was investigated by using x-ray diffraction (XRD) for the structural analysis and by using an impedance analyzer (LCR meter) for the electrical conductivity and dielectric properties in frequency range from 20 Hz to 1 MHz. The temperature effect of PVA-PPy-FeCl3 of composites and the radiation effect of PVA-PPy-CH and PVA-PPy-TCA composites on electrical conductivity and dielectric properties were also investigated. The XRD analysis for the samples at different composition of the dopants indicated that the redox mechanism had been taken placed particularly for polypyrrole pellets as it clearly showed that the peak presence of the dopant. On the other hand, for PVA-PPy-FeCl3 composite films, it was observed that the broad peak of PVA was diminished as a result of the competition between insulating PVA and PPy formation, in which PPy yield becomes higher at higher concentration of the dopant. The gamma ray induced PVA-PPy-TCA and PVA-PPy-CH composite films gave the same trends for both of the samples. The broad peak of PVA was present for all samples. New peak was observed upon irradiation particularly for higher composition of the dopant. It was attributed to the radiation scission of TCA and CH molecules, which do not involve in PPy polymerization as all of the Py monomers were already consumed. The electrical conductivity, σ for all samples increased with the increase of dopant composition, temperature and irradiation dose. Polypyrrole pellets contained highest conductivity among the others, as they do not contain insulating polymer binder in which could reduce the magnitude of conductivity. Among PPy composite films, PVA-PPy-FeCl3 gave better conductivity as compared to PVA-PPy-TCA and PVA-PPy-CH due to factor of FeCl3 in which it is known that iron (III) chloride is reactive electron acceptor and the reason that it is genuinely oxidation agent in which TCA and CH do not own. Therefore, gamma-rays were used to induce the electrical properties of TCA and CH doped polypyrrole composites. The gradual increase of the conductivity as increase the dopant concentration and irradiation dose can be attributed to more free charges (i.e. polarons) available in the composite system whereas for temperature dependent study, the conductivity increased as the temperature increased, was due to the high mobility of free charges interact in composite system. Dielectric properties in respect of relative permittivity (dielectric constant), ε’ and loss permittivity (dielectric loss), ε” showed that the value increased as the dopant composition, temperature and irradiation dose were increased. The number of dipoles available became prominent as the dopant and irradiation dose were increased thus increase the value of dielectric properties. On the other hand, the value for relative permittivity and loss became higher as the temperature was increased, attributed to the higher mobility of dipoles in the composite system. The trend for all samples; PPy pellets and composites films, were almost similar as at the lower frequency region (~ 20 Hz to 1 kHz), sharp decrease were observed due to the dipoles orientation along applied electric field and reaching almost a constant value at higher frequency (~ 1 kHz to 1 MHz) region. It was due to the difficulty of the dipoles to orient themselves as the applied frequency became higher. The relaxation time, τ (ω) in which represents dielectric relaxation obtained for all samples, almost reduced with the dopant composition, irradiation dose and temperature. Such an inconsistent value of τ (ω) might be due to the uncertain value of the angular frequency peak, ωp and irregularity of the electrical displacement.